Analisis Preferensi Penggunaan Moda Kereta Api Bandara Menuju New Yogyakarta International Airport - Setiawan, Danny (Semesta Teknika, 2018)
Relocation Adisutjipto Airport to New Yogyakarta International Airport (NYIA) within Â±45 km from Yogyakarta city center by airport train as a liaison transportation modal, it is needed the research of passenger preferences in transportation modal choice analyze to NYIA. Data collection methods used by stated preference (SP) and analyzed by ordered probit model. The results showed ideal distance of air passengers which willing to use the airport train when the airport distance to the city about 37 km. The airplane passenger willingness to pay (WTP) that state â€œdefinite useâ€ airport train is about 56.00% for alternative 8. The WTP of airport train NYIA is IDR 50.067 with priority level of service is punctuality. The congestion condition from Yogyakarta city to NYIA airport will decrease 46.75% because the passenger using airport train.